Pendekatan Obyektif Dalam Tafsir Penciptaan Alam - Adudin Alijaya (Al Burhan: Jurnal Kajian Ilmu dan Pengembangan Budaya Al-Qur'an, 2018)
There are many verses that seemed to be unidirectional within Al-Quran which have implications for varied understanding and tend to be contradictory. An example is a verse about the creation of nature about the duration of “day”. But with the understanding of the verse, to get the meaning of the verse it is necessary to have a particular approach in understanding it, namely by linguistic approaching. A linguistic approach can be carried out if an uneven analysis of verses with other verses in one or the same letter is not possible. So, if it is still possible to find a verse that is correlated with that verse, then a linguistic approach is not needed. Basically a language approach in the study of interpretation, only one of several approaches, each of which has advantages or disadvantages.